Comparison Of Providing Education Using Leaflet And Video Media On The Level Of Understanding Of Hypertension Sufferers About The Dash Diet - Erika Joyce Anastasya; Oda Debora; Ellia Ariesti; Febrina Secsaria Handini (Jurnal Keperawatan Malang, 2023)
Background:Hypertension is a disease with high prevalence and tends to be followed by many comorbid. One of hypertension management is non-pharmacologic therapy by managing diet using a DASH mealplan. To give a better comprehension of the DASH diet, education is needed. Objective:The aim of this research. A was to compare the comprehension level of the DASH diet among hypertension patients which was given information through leaflets and video Methods:The method in this study was cross-sectional, with 32 respondents who had been selected using a purposive sampling technique. Respondents were divided into two groups, namely 16 recipients of information on the DASH diet using leaflets and 16 recipients of information via video media. Furthermore, data on the level of understanding of the DASH diet were measured and analyzed using the Mann-Whitney method through the SPSS version 26 program. Results:The results of this study show differences in understanding between leaflet media and video media. The result shows that (p-value 0.028). Conclusion:The use of educational media is an important factor which contributes to the level of comprehension in addition to other factors that also have an important influence on the level of comprehension, namely the level of education, age, gender and comorbidities that exist in people with hypertension. Keywords: hypertension, DASH diet, health education, comprehension, leaflet, video.